(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Both maternal nutritional status and GDM have impact on pregnancy outcome. But, data from Bangladesh in this issue is still scarce. To design and utilize national obstetric health care, nutritional status of GDM women and its impact in the birth weight of babies should be evaluated and therefore, this study was designed. Methods: This prospective cohort study was conducted in the department of Obstetrics and Gynecology at BIRDEM General Hospital-2, Dhaka to evaluate the nutritional status of GDM women and its impact on pregnancy outcomes. Results: The mean age of the patients in the study was 29.71± 5.06 years. The mean age, Mid Upper Arm Circumference (MUAC,) and Body Mass Index (BMI) were significantly higher in GDM mothers (p <0.05). Additionally, gestational weight gain between 28 weeks and before delivery was significantly higher in GDM mothers (p <0.001). The mean birth weight of the newborns was also higher in the GDM group (3.23±0.46vs. 2.97±0.37 kg) (p <0.05). Macrosomic neonates were observed only in the GDM group (4.36%). APGAR score was significantly better in non-GDM mothers’ babies (p <0.05). Babies of GDM mothers had a significantly higher proportion of birth asphyxia, septicemia, pneumonia, Intrauterine Growth Retardation (IUGR), and Neonatal Intensive Care Unit (NICU) admissions (p <0.05). Macrosomic mothers had significantly higher BMI and higher gestational weight gain (p<0.05). Conclusion: Mothers with GDM had a higher rate of bad pregnancy outcomes and that macrosomia was linked to a higher BMI. J Bangladesh Coll Phys Surg 2023; 41: 63-74